Quantum-critical spin dynamics in a Tomonaga-Luttinger liquid studied with muon-spin relaxation - Möller, J; Lancaster, T; Blundell, S; Pratt, F; Baker, P; Xiao, F; Williams, R; Hayes, W; Turnbull, M; Landee, C (American Physical Society, 2017)
We demonstrate that quantum-critical spin dynamics can be probed in high magnetic fields using muon-spin relaxation (μ+SR). Our model system is the strong-leg spin ladder bis(2,3-dimethylpyridinium) tetrabromocuprate (DIMPY). In the gapless Tomonaga-Luttinger liquid phase we observe finite-temperature scaling of the μ+SR 1/T1 relaxation rate which allows us to determine the Luttinger parameter K. We discuss the benefits and limitations of local probes compared with inelastic neutron scattering.